Evaluation of Closure versus Non-closure of Vaginal Vault after Non-descent Vaginal Hysterectomy - Saha, Mousumi; Rahman, Ratu Rumana Binte; Ara, Gulshan; Rahman, Florida; Jahan, Raunak (Journal of Shaheed Suhrawardy Medical College, 2021)
Introduction: Non-descent vaginal hysterectomy has been considered a valid alternative to the abdominal approach and is also preferred for benign uterine diseases without descent of uterus because it is associated with fewer complications. Vaginal vault is the enlargement of the internal end of the vagina which is usually closed during vaginal hysterectomy. This study was done to see the outcome of vault closure versus non-closure in non-descent vaginal hysterectomy in non-prolapsed uterus. Methods: This prospective study was done in Obstetrics and Gynae Department, Sir Salimullah Medical College and Mitford Hospital during the period of July 2011 to December 2011. A total number of 50 patients with benign gynecological disorders without descent of uterus who admitted for hysterectomy were enrolled in this study. Among them, 25 patients had the vault close (group I) whereas 25 patients had an open vault(group11). Indication for hysterectomy, complications, blood transfusion, hospital stay (day) and histopathological findings were assessed for both groups. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20). Results: Majority of the patients was found in the age group of 41-45 years in both groups, which was 12(48.0%) in Group I and 18(72.0%) patients in Group II. Blood transfusion was needed in 5(20.0%) and in 6(24.0%) in Group I and Group II respectively. Post operative complications after 15 days of follow-up, pelvic abscess was found 4.0% in Group I & not found in Group II. UTI was not found in Group I but 4.0% found in Group II. Conclusion: Outcomes were almost similar in both procedure. Ultimately the study did not show any significant difference between either group. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 45-49